2019
DOI: 10.17233/sosyoekonomi.2019.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Does Flypaper Effect Exist? New Evidence from Turkish Municipalities

Abstract: In this paper, we investigate the phenomenon of flypaper effect and its relation to the local tax effort, by using a new and detailed panel data set that consist of all province and district municipalities' fiscal data in Turkey between 1997 and 2005. We use fixed effects and dynamic panel data specific GMM estimators to obtain the results. We provide new evidence using an advanced technique which is firstly used to uncover flypaper effect in Turkey. According to our estimations, the flypaper effect does exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
(20 reference statements)
1
5
0
1
Order By: Relevance
“…The finding coincides with the results achieved in De Mello (2000), Bastida et al (2009), Köppl-Turyna and Pitlik (2016), Faulk andKillian (2017), andPadovani et al (2018). In addition, this finding supports the flypaper effect, which has been proven to be valid in municipalities in Turkey by Sağbaş and Saruç (2004), Aytaç (2015), Yaş and Akduğan (2015) and Acar (2019). With this effect, the expenditures of local administrations increase more than the own revenues of grants or the efforts of the executives to collect taxes decrease.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The finding coincides with the results achieved in De Mello (2000), Bastida et al (2009), Köppl-Turyna and Pitlik (2016), Faulk andKillian (2017), andPadovani et al (2018). In addition, this finding supports the flypaper effect, which has been proven to be valid in municipalities in Turkey by Sağbaş and Saruç (2004), Aytaç (2015), Yaş and Akduğan (2015) and Acar (2019). With this effect, the expenditures of local administrations increase more than the own revenues of grants or the efforts of the executives to collect taxes decrease.…”
Section: Discussionsupporting
confidence: 88%
“…With this effect, the expenditures of local administrations increase more than the own revenues of grants or the efforts of the executives to collect taxes decrease. Acar (2019) reached both findings in his study. Therefore, the increase in expenditures and the decrease in revenues depending on the shares transferred from the general budget tax revenues will cause a budget deficit and the need for borrowing.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…At the same time, it is concluded that capital expenditure has a positive effect on society welfare in district with extreme degree of fiscal decentralization. Yacoub and Lestari (2019) also found that the flypaper effect was valid for districts and cities in Kalimantan Island of Indonesia in the period 2013-2016. Acar (2019 reached the conclusion that there was the flypaper effect in Turkey and that the unconditional fiscal transfers had substitution effect on revenue collection efforts of municipalities through panel data set of municipalities in the period of 1997-2005. There are also studies on the symmetrical or asymmetrical structure of the flypaper effect.…”
Section: Empirical Literature Reviewmentioning
confidence: 96%